Collateral damage. (Economist, 1996)
Discusses the impact on Sun Microsystems of Netscape's battle with Microsoft for the World Wide Web browser market. Java, Sun's programming language, which gained a great deal of popularity with Netscape's help; Two reasons for the fact that Sun is not directly threatened by the prospect of a Microsoft victory; Sun's plans to join the low-end consumer software market; Worldwide server operations system shipments in 19 and forecasts for 1996 and 1997.